The Influence of Financial Literacy and Social Media on Gold Investment Interest Through Costumer Trust BSI Malang SOETTA - Yulitasari Mila Dewi; Ronny Malavia Mardani; Nurhidayah (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of financial literacy on trust, analyze the influence of social media on trust, analyze the influence of financial literacy on investment interest, analyze the influence of social media on investment interest, analyze the influence of trust on investment interest, and analyze the influence of financial literacy on investment interest through trust. The sample in this study involved 183 customers. The data analysis technique used AMOS. The results of the analysis show that financial literacy influences trust. Social media influences trust. Financial literacy influences investment interest. Social media influences investment interest. Trust influences investment interest. Financial literacy influences investment interest through trust. Social media influences investment interest through trust.